Prevalence and Factors of Diabetic Retinopathy in Makarak Hospital - Thaithanan, Bussaba (Journal of Health Science of Thailand, 2018)
To investigation the prevalence and factors for diabetic retinopathy (DR) in diabetes patients of Diabetes clinic in Makarak Hospital a clinic-based retrospective study were performed on 2,852 patients from January 2003 to December 2007. DR was presented in 23.38 percent which were NPDR in 496 patients (17.39%) and PDR in 171 patients (5.99%). Duration of diabetes, fasting blood glucose level, male sex and age were possibly associated with increased risk of retinopathy. Several other factors including hypertension, dyslipidemia and especially proteinuria had significant association with DR.